Unambiguous Base Station Identifier Code in Widely Picocells area using Golay Complementary Sequence (Al-Mansour Journal, 2022)
The wireless communication system has at least one picocell within macrocell. The use of picocell gives many advantages, savinga radiation power, increase the capacity and improve the dead zone. However, in a system where a large wide-area cell overlapped with many of picocells, many of the picocells will have to re-use the same Base Station Identifier Code (BSIC- small number of bits). Hence, when an MS roams from the wide-area cell into a target picocell, the reported BSIC may be ambiguous. The optimal operating point of the combination above was obtained by analysis of cell distribution. This paper presents a new algorithm to classify the user according to mobility narrow and widely, then use Golay code complementary sequences for widely mobility user and implement a tracker circuit to track the user for accurate handover decision. The accuracy is satisfied by using Golay code and by tracking the user. Furthermore, the implementation of Golay code creator, correlator and tracker circuit by using Xilinx-spartan-3A XC3S700AFPGA, with 50 MHz internal clock is supported for increasing the speed of operation and accuracy.
Keywords: Wireless communication; Picocell; re-use distance; Golay sequences; FPGA-Spartan